القضية الكردية وتداعياتها على الأمن القومي في تركية - عبد العزيز أيمن; غزالي بهاء (Latakia University Journal - Economic and Legal Sciences Series, 2016)
This study examined the Kurdish issue in all its dimensions and its implications as one of the most Turkish national security challenges. The political and military authorities in Turkey Were ignored the Kurdish demands political, social and cultural, Under the pretext of Turkish national security. the Turkish governments continued for decades to deny the existence of a Kurdish issue or described as "terrorism" or described as a" conspiracy" by the West. So the majority of the policies of the Turkish government used military force to hit PKK strongholds, At present the Turkish political authorities have realized the it is no longer feasible to use military force in dealing with the Kurdish issue, and is no longer possible to ignore the Kurdish demands, Especially that the West began to sympathize with the Kurds and their cases. And considered it as a gate of the democracy and the condition of Turkish entry to the EU. As well as the Turkish Kurds today whether owned the importance of the demographic, social, economic, military, political and information within and outside Turkish. but The most prominent event on the Turkish national security impact directly and the form of the most prominent challenges is the establishment of an independent Kurdish entity federal powers independent State on the border with Turkish state, The Justice and Development Party stressed that the Kurdish issue is one of the most important concerns and public policy problems in Turkish, and it is one of the main sources of threat to stability in Turkish if not resolved drastically Through military, security solutions, and economic development, and The interest in South-East Turkey, and the democratization of political life and promote legislative changes, legal, and constitutional amendments. تناولت الدراسة القضية الكردية بأبعادها وتجلياتها بوصفها إحدى أبرز تحديات الأمن القومي التركي. فبمرور الوقت تعقدت القضية الكردية واكتسبت أبعاداً تصعب مواجهتها والاقتراب من فواعلها. ففي الوقت الذي كانت فيه معظم النخب الحاكمة في تركية تتجاهل مطالب الأكراد السياسية والاجتماعية والثقافية لاعتبارات تراها تلك النخب تتعلق بالأمن القومي التركي وتعتبرها تقويضاً لأسس ومرتكزات الدولة التركية الحديثة التي أسسها مصطفى كمال أتاتورك، مع استمرار إنكار وجود قضية كردية أو نعتها" بالإرهاب" أو اعتبارها وليدة "مؤامرة" من قبل الغرب. فقد اتبعت الحكومات التركية سياسات اتسمت غالبيتها باستخدام القوة العسكرية لضرب معاقل حزب العمال الكردستاني، ما قاد إلى دائرة من العنف لاتنتهي. وتحولت القضية الكردية إلى جرحٍ نازف في ماض وحاضر ومستقبل الدولة التركية، أما في الوقت الحاضر فقد أدركت النخب الحاكمة التركية أنه لم يعد مجدياً استخدام القوة العسكرية في التعامل مع المسألة الكردية, ولم يعد ممكناَ تجاهل المطالب الكردية التي بدأت تلقى آذاناً صاغية لدى الغرب, و بات يعتبرها بوابة الديمقراطية والشرط الأساسي لدخول تركية إلى الإتحاد الأوربي. فضلاَ عما يمتلكه أكراد تركية اليوم من ثقل ديمغرافي وسياسي وإعلامي واجتماعي واقتصادي وعسكري واسع داخل تركية وخارجها. والحدث الأبرز الذي ألقى بظلاله على الأمن القومي التركي وشكل أبرز تحدياته هو قيام كيان كردي فدرالي مستقل يتمتع بصلاحيات الدولة المستقلة على الحدود المتاخمة للدولة التركية التي يعيش فيها غالبية أكراد العالم. الأمر الذي دعا حزب العدالة والتنمية إلى اعتبار المسألة الكردية هي أحد أهم شواغل ومشاكل السياسة العامة في تركية، وأنها تشكل أحد مصادر التهديد الرئيسة للاستقرار في تركية إذا لم تعالج بشكل جذري يتم من خلاله التوصل إلى تسوية للأزمة ببعديها الأمني والعسكري أولاً، ثم ببعديها التنموي والاقتصادي، وضرورة اقتراح رؤى جديدة لتركية قائمة على الالتفات إلى جنوب شرق تركية والانفتاح الداخلي عليها، ودمقرطة الحياة السياسية وتعزيزها بتغييرات تشريعية وقانونية، وتعديلات دستورية.